Neurological complication after oncological treatment - Nagańska, Ewa (Przewodnik Lekarza/Guide for GPs, 2007)
Neurological complications after oncological treatment may appear during therapy as early complications or after therapy as delayed events. Some neurological post-treatment symptoms are characteristic for special types of therapy, but most of them have similar course in most patients. In the case of surgical treatment or radiotherapy of neoplastic tumours of the brain or head and neck, the risk of complications is directly connected with location of tumour. In the case of chemotherapy the complications follow the use of cytostatic drugs, independently of the type and location of tumour mass. Instead of great progress in methods of oncological treatment the subject of post-treatment complications should still be in the minds of researchers. The question of early diagnosis and methods of prophylaxis remain very important.